2005
DOI: 10.1111/j.1744-7348.2005.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen fertilisation and regrowth period on fatty acid concentrations in perennial ryegrass (Lolium perenne L.)

Abstract: Information on lipids in forages is scarce, and effects of nitrogen (N) application level and regrowth period on the fatty acid (FA) concentration and composition of perennial ryegrass (Lolium perenne L.) were studied. N was applied at 0, 45 and 100 kg ha 21 , and swards were cut after various regrowth periods, resulting in six treatments designed as randomised blocks with three replicates. The stages of development ranged from vegetative to elongating swards, with herbage yield levels from 1.9 to 4.2 t dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 25 publications
9
49
1
2
Order By: Relevance
“…This is partly in agreement with findings from earlier studies (Boufaïed et al, 2003b;Elgersma et al, 2005;Witkowska et al, 2008). Boufaïed et al (2003a) found positive linear relationships between the N concentration and 16:0, 18:2n-6, 18:3n-3 and total FA in timothy.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is partly in agreement with findings from earlier studies (Boufaïed et al, 2003b;Elgersma et al, 2005;Witkowska et al, 2008). Boufaïed et al (2003a) found positive linear relationships between the N concentration and 16:0, 18:2n-6, 18:3n-3 and total FA in timothy.…”
Section: Discussionsupporting
confidence: 92%
“…This could explain the linear increase in 18:0 concentrations in milk with increasing N fertilisation. Further, the WSC concentration was inversely correlated with the CP concentration in the grass silages, with G-30 resulting in significantly higher WSC intake than the other silages (Table 2 and 4), which is in accordance with Elgersma et al (2005) who found the same trend in perennial ryegrass. Lee et al (2003) found in an in vitro experiment that a high inclusion of WSC in the diet induced a shift towards fermentation of WSC rather than fibre digestion, which suggests a shift away from fibrolytic bacteria.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Regrowth periods affected the total milk FA concentration in our trial with significantly lower concentrations of C18:3 after a longer period of regrowth in the G/S compared to the G group. Elgersma et al (2005) also hypothesized that the protein content in the herbage, the leafblade proportion of the canopy and regrowth period of the sward, might affect milk fat content and proportions of FA in the herbage. The milk CLA response was also related to the PDMI, CP and IVODM of swards increasing from the G/S group to the G group.…”
Section: Effect Of Forage Source On Conjugated Linoleic Acid Content mentioning
confidence: 99%